Sustainable transition of food consumption in rural China: spatio-temporal patterns and drivers of carbon footprint - Huibo Qi; Huibo Qi; Yeyi Guo; Peng Ji; Fei Long; Fei Long; Jing Zhao; Jing Zhao (Frontiers in Sustainable Food Systems)
Since achieving basic food security and poverty alleviation in rural areas in 2000, China has experienced rapid growth in rural residents’ incomes, prompting increased scrutiny of food consumption sustainability. This study examines the transition in food consumption patterns of rural residents in China from 2001 to 2023. It quantifies their food consumption carbon footprint (FCCF) using the carbon conversion factor method and analyzes spatio-temporal patterns and drivers by integrating an extended STIRPAT framework with spatial econometric models. Three main findings emerge: First, spatio-temporal patterns reveal persistent structural imbalances in food consumption, with per capita FCCF showing a fluctuating upward trend. Second, per capita FCCF demonstrates significant spatial agglomeration, characterized by “high-high” and “low-low” clusters. Third, population, affluence, technology, trade, and food consumption structure all significantly influence per capita FCCF, albeit with notable regional variations. Identifying key drivers and their spatial spillovers offers valuable insights for tailoring region-specific policy interventions.